جريمة التزوير في التشريع الجزائري على ضوء أحكام القانون 24-02 - أميرة ماجري (My University, 2025)
This memorandum addresses the provisions of Law No. 24-02 concerning the crimes of forgery and the use of forged documents. This study delves into defining the conceptual framework of these two offenses by elucidating their definitions and legal el ements, distinguishing between them and related legal concepts, and detailing their various forms and the types of documents that can be the subject of forgery. The memorandum also examines the relevant criminal procedures, commencing with the determination of the scope of judicial jurisdiction and the precautionary measures taken, proceeding through the mechanisms for initiating public prosecution and the role of the Public Prosecutor's Office in this regard, and culminating in the procedural means available for uncovering these crimes, such as search procedures, expert opinions, and evidence gathering. In concluding the analysis, the study pays particular attention to defining the legal frameworks for the penalties prescribed for the crimes of forgery and the statute of limitations for the public action arising therefrom, while clarifying the material and personal scope of criminalization. Overall, this memorandum aims to provide a comprehensive legal analysis of the crimes of forgery and the use of forged documents within the Algerian legal system, taking into account the challenges and emerging developments posed by modern technological advancements ............................... تناولت هذه المذكرة أحكام القانون 24/02 المتعلقة بجرائم التزوير واستعمال المزور، حيث تطرقت هذه الدراسة إلى تحديد الإطار المفاهيمي للجريمتين، وذلك بتبيان تعريفهما وأركانهما القانونية، والتمييز بينهما وبين المفاهيم القانونية ذات الصلة، فضلا على تفصيل مختلف صورهما وأنواع المحررات التي يمكن أن تكون محلا للتزوير، كما تناولت المذكرة الإجراءات الجزائية ذات الصلة، بدءا بتحديد نطاق الاختصاص القضائي والتدابير الاحترازية المتخذة، ومرورا بآليات تحريك الدعوى العمومية ودور النيابة العامة في هذا الشأن، ووصولا إلى الوسائل الإجرائية المتاحة للكشف عن هذه الجرائم، كإجراءات التفتيش والخبرة وجمع الأدلة، وفي ختام التحليل أولت الدراسة اهتماما خاصا بتحديد الأطر القانونية للجزاءات المقررة لجريمتي التزوير وتقادم الدعوى العمومية الناشئة عنهما، مع تبيان النطاق الموضوعي والشخصي للتجريم، تهدف هذه المذكرة في مجملها إلى تقديم تحليل قانوني شامل لجرائم التزوير واستعمال المزور في المنظومة القانونية الجزائرية مع مراعاة التحديات التطورات المستجدة التي بفرضها التطورات التكنولوجية الحديثة. .......................... Ce mémorandum porte sur les dispositions de la loi n° 02/24 relatives aux délits de faux et d'usage de faux. L'étude aborde le cadre conceptuel de ces deux infractions, clarifiant leurs définitions et leurs éléments juridiques, les distinguant des concepts juridiques connexes et détaillant leurs différentes formes et les types de documents susceptibles d'être falsifiés. Le mémorandum aborde également les procédures pénales applicables, en commençant par la définition du champ de compétence judiciaire et des mesures conservatoires prises, puis en abordant les mécanismes d'engagement de l'action publique et le rôle du ministère public à cet égard, et enfin les moyens procéduraux disponibles pour détecter ces infractions, tels que les procédures d'inspection, d'expertise et de collecte de preuves. Enfin, l'étude accorde une attention particulière à la définition du cadre juridique des sanctions prévues pour les délits de faux et à la prescription des poursuites publiques qui en découlent, tout en clarifiant la portée objective et subjective de l'Incrimination. Ce mémorandum vise, dans son intégralité, à fournir une analyse juridique complète des délits de faux et d’usage de faux dans le système juridique algérien, en tenant compte des défis et des évolutions imposés par les avancées technologiques modernes.
Keywords: Legal keywords Forgery Use of forged document Witings Statute of limitation Sanctions Criminal intent; الكلمات المفتاحية التزوير استعمال المزور المحررات التقادم الجزاءات القصد الجنائي; Mots clés faux Utilisation de documents documents prescription sanctions Intention criminelle